Understanding the molecular mechanism of improved proliferation and osteogenic potential of human mesenchymal stem cells grown on a polyelectrolyte complex derived from non-mulberry silk fibroin and chitosan. (7th December 2017) - Bissoyi, Akalabya; Kumar Singh, Abhishek; Kumar Pattanayak, Subrat; Bit, Arindam; Kumar Sinha, Sudip; Patel, Ashish; Jain, Vishal; Kumar Patra, Pradeep
Abstract: The development of engineered bone tissue, as a promising alternative to conventional bone grafts, has so far not proven successful and still remains challenging. Thus, attempts have been made in the present study to synthesize polyelectrolyte complex (PEC) scaffolds by blending chitosan (CS) to silk fibroin (SF) derived from the non-mulberry silkworm ( Antheraea pernyi ) at three different pH values (5.0, 6.0, and 7.0), and to characterize them in terms of morphology, ultrastructure and mechanical properties with scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy, x-ray diffraction and tensile strength analyses. The prepared PEC scaffolds showed a mean pore size of 130 μ m, as revealed by SEM analysis, and a comparatively higher compressive strength. The findings of in vitro cytocompatibility, in vivo biocompatibility and osteogenic marker (genes/proteins) analysis suggest that the PECs blended at pH 7.0 showed greater stability and enhanced growth and an osteogenic differentiation capability of human mesenchymal stem cells (MSCs). To aid our understanding of protein–polyion binding mechanisms, we employed a molecular docking and simulation study of SF macrodomains and CS oligomer using Schrödinger 14 and GROMACS (Groningen Machine for Chemical Simulations) software. The study involved analytical techniques for macromolecular solution characterization and theoretical simulations based on molecular dynamics. The computational studies confirmed the presence of an integral RGD sequence that played a vital role in superior cell-attachment, proliferation and osteogenic differentiation of MSCs grown on the developed SF–CS PEC scaffolds.